Implementation of Online SIM Applications in Improving Public Services by the Implementing SIM Administration Unit (Satpas) Police Unit - Almuraj, Muhtadibillah (Police Studies Review, 2024)
SIM Online Services as a creative breakthrough is one of the community service tasks carried out by the Cirebon City Police Task Force to answer the community's needs in completing and completing SIMs stipulated in Number 22 of 2009 concerning Road Traffic and Transportation. This study uses qualitative survey methods that aim to find out 1) the implementation of the SIM Online application in improving public services; 2) Strategy of the Satpas as the operator of the SIM Online application in increasing public satisfaction; and community satisfaction in the application of an online SIM application. Research respondents were 23 people who applied for SIM services and 7 officials and SIM service officers at the Cirebon City Police Task Force. Research data collection using interview, observation, and questionnaire methods. The research data were analyzed with qualitative and triangulation descriptive techniques. The results of this study found that the SIM application was conducted online based on standard SOPs and at the Satpas at the Cirebon City Police Headquarters with an inadequate area for a practical examination. The strategy taken to increase community satisfaction is through internal and external outreach programs, requesting services to the community, and traffic conscious and orderly campaigns. Community satisfaction in the application of online SIM applications is quite good. Some things that need to be improved are application and application menu display, data transfer transfer, document format, and SIM function as SIM.